OPTIMIZATION SPORES PRODUCING β-KAROTEN OF FUNGUS Neurospora sitophila BY RESPONSE SURFACE METHOD (On Fermentation Process Duration and Starter Concentration) - Novianti, Trisita; Wignyanto, Wignyanto; Nurika, Irnia (Jurnal Teknologi Pertanian, 2004)
Supplying nutrient was still difficult problem in developing countries like Indonesia, one of them was the lack of supplying vitamin A. Provitamin A source, especially β- karoten, much β-karoten could be gotten from fruits and vegetables which have yellow or green colour, the others alternative of supplying vitamin A could be gotten from fungus Neurospora sitophila strain in solid tofu waste medium on fermentation process duration and starter concentration which have been adjusted in optimal condition Experimental design used central composite design with two factors (fermentation process duration and starter concentration of fungus Neurospora sitophila) and two responses (β-karoten concentration and spores amount). Variables of fermentation process duration factor were 5,172 days, 6 days, 8 days, 10 days, and 10,828 days, while variables starter concentration factor were 1,757%, 3%, 6%, 9%, and 10,243%.  Analysis which have done, were: β-karoten analysis, spores amount analysis, pH analysis, moisture content analysis, and optimization by response surface method were the research process. The counting result were β-karoten concentration of fungus Neurospora sitophila response had quadratic model Y =  86,18265 + 7,63485 X1 + 1,67998 X2 – 0,41042 X12 –0,086288 X22 – 0,062833 X1X2 with R2 = 95,06% and spores amount of fungus Neurospora sitophila response had quadratic model Y = 10,77813 + 0,11552 X1 + 0,023106 X2 – 6,85906.10-3 X12 – 2,13736.10-3 X22 + 7,79167.10-4 X1X2 with R2 = 98,28%. For the applying of industry, the result of optimal β-karoten concentration was 125,2408 ppm with optimal spores amount was 11,3682 log spora/ml, while optimal fermentation process duration was 9 days with optimal starter concentration was 6,8%.   Key Word : β-karoten, Neurospora sitophila